지식정보화 사회의 성숙과 IT산업이 농업에 미치는 영향 - 최영찬 (한국농촌경제연구원, 2007)
Today we are living in the society of information. Information industry is growing fast and the information technology is improving rapidly. Information become the most important resource and infrastructure for the society. As the role of the information increases, most countries compete to build better information infrastructure and develop information intensive technology. For the last 20 years, many institutions in Korea have tried to build more effective agricultural information system. They have devoted most effort to build DB/NWs for agribusiness, farmers, and rural community. With bigger challenges ahead, Korean agriculture need further effort to pursue the information intensive agro-food business industry. This book projects the future of information technology and their impacts on agriculture and food industry It will provides plausible paths and development ahead for agribusiness and rural community with rapid innovations in information technology. Korean agriculture and food business sector has more reason to need information system, including shortages in traditional resources, opening the domestic market to world, and changes in agribusiness organizations. Korean agribusiness kept labor intensive management system traditionally since land and capital were scarce resources. However, as farm population decreases and gets old continuously, Korean agribusiness now faces shortages in all three traditional resources. Dickson has long been argued for the importance of information as nontraditional resource for modern business. In this information age, the role of nontraditional resource surpasses the role of traditional resources for the competitiveness of modern business. We need to invest more for expanding the information resource and hence for compensating the inferior traditional resources. Authorities and private sectors should together put all their efforts to build agriculture as information intensive industry. Korean agricultural sector and rural community now faces real challenge with various free trade agreement to be settled. Structural changes are spreading widely in Korean agribusiness lately. They are integrating horizontally as well as vertically. Many agribusiness organizations expand their business processes from production to processing and marketing. These changes increase flexibility, location independence, and empowerment of organization. They also increase collaborative work and teamwork which lower transaction and coordination costs. Better information system promotes these positive environment. Small scale Korean agribusinesses have disadvantages to compete in free trade environment with large scale agribusinesses from abroad. Integration of the widely distributed small agribusinesses can be efficiently done with better information system and network. Using various new technologies including RFID, USN, GPS, e-CRM, robotics, artificial intelligence, machine learning, new generation sensors, IPTV, Web 2.0 solutions, imbedded SW, high speed communication tools and network technologies, remote sensing and convergence of technologies, farmers and agribusiness managers can monitor and control whole value chains, including production, processing, storages, and marketing. Various type of ECs and online trading can help agribusiness to keep their own brand and prices. Fast and consistent communication infrastructure will help the small business of farms to integrate vertically and horizontally easily. It will also makes remote conference and control easier and hence reduce socio-cultural gap between urban and rural area with remote medical operation, teaching, and cultural performance. Improved robotics and artificial intelligence will allow farmers to increase size of their farm with automated production facilities and equipments. These IT based agriculture will allow us to build more competitive future. Researchers: Choe, Young Chan Research period: 2007. 8 ~ 2007. 11. E-mail address: a99i@snu.ac.kr